Assessment and Interventions for Vascular Injuries Associated With Fractures. Issue 9 (1st May 2022) - Spitler, Clay A.; Patch, David A.; McFarland, Graeme E.; Smith, Walt R.
Abstract : Vascular injuries associated with fractures are limb-threatening injuries with notable morbidity. The prompt and thorough evaluation of these patients is imperative to diagnose vascular injuries, and coordinated multidisciplinary care is needed to provide optimal outcomes. The initial assessment includes a detailed physical examination assessing for hard and soft signs of arterial injury, and the arterial pressure index can be used to reliably identify vascular compromise and the need for additional assessment or intervention. Advanced imaging in the form of CT angiography is highly sensitive in additional characterization of the potential injury and can be obtained in an expedient manner. The optimal treatment of fractures with vascular injuries includes providing skeletal stability and confirming or reestablishing adequate distal perfusion as soon as possible. Options for vascular intervention include observation, ligation, direct arterial repair, vascular bypass grafting, endovascular intervention, and staged temporary shunting, followed by bypass grafting. Although the optimal sequence of surgical intervention remains an incompletely answered question, the orthopaedic role in the care of patients with these injuries is to provide mechanical stability to the injured limb to protect the vascular repair and surrounding soft-tissue envelope.